143 Predictors of depression 6 months following MS relapse. Issue 3 (9th February 2012) - Moore, P; Hirst, C L; Clarkson, H; Baker, K L; Luppe, S; Pickersgill, T P; Robertson, N P
Abstract : Background: Relapses are associated with an increase in disability for the majority of patients and many patients do not subsequently recover completely. However, the impact of post relapse changes in disability on mood in MS is currently unresearched. Objective: To investigate the predictive ability of disability at relapse, depression at relapse and post-relapse changes in disability on depression ratings 6 months post-relapse. Methods: 139 participants were assessed for disability level on the Expanded Disability Status Scale (EDSS) and mood on the depression scale of the Hospital Anxiety and Depression Scale (HADS) during a confirmed MS relapse and 6 months post relapse. Results: At relapse 45.5% of participants met criteria for possible depression on the HADS. This reduced to 34.4% at 6 months. A stepped backward logistic regression demonstrated that depression and disability status at relapse were significant predictors of depression at 6 months but 6 month disability level did not predict depression. Patients likely depressed at relapse were substantially more likely to be depressed at 6 months than those not depressed at relapse (OR 11.9). Conclusions: Depression at relapse appears to be a stronger predictor of depression 6 months post-relapse than disability level or changes in disability. Assessment of depression at relapse may identify individuals who might benefit from subsequent intervention.